2013
DOI: 10.1007/s00264-013-2219-4
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin prevented IL-β-induced expression of inflammatory mediators in human osteoarthritis chondrocytes

Abstract: Purpose Cordycepin, a nucleoside derivative isolated from Cordyceps, has been reported to exert anti-inflammatory, antitumor, antidiabetic and renoprotective effects. Osteoarthritis (OA) is a degenerative joint disease with an inflammatory component that drives the degradation of cartilage extracellular matrix. This study aimed to assess the effects of cordycepin on human OA chondrocytes. Methods In this study, human OA chondrocytes were pretreated with cordycepin at 10, 50 or 100 μM and subsequently stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…These inflammatory mediators are implicated in bone resorption and joint pain [23]. Accumulating evidence suggests that inhibition of these inflammatory mediators has therapeutic potential in the treatment of OA [8,24]. In this study, our results showed that astragalin inhibited IL-1β-induced NO and PGE2 production, as well as iNOS and COX-2 expression in chondrocytes.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These inflammatory mediators are implicated in bone resorption and joint pain [23]. Accumulating evidence suggests that inhibition of these inflammatory mediators has therapeutic potential in the treatment of OA [8,24]. In this study, our results showed that astragalin inhibited IL-1β-induced NO and PGE2 production, as well as iNOS and COX-2 expression in chondrocytes.…”
Section: Discussionmentioning
confidence: 55%
“…Overproduction of NO and PGE2 leads to clinical manifestations [7]. Accumulating evidence suggests that neutralization of IL-1β-induced inflammatory mediators appears to be useful in the treatment of OA [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…It has been known that MAPK signaling pathway has a critical role in the regulation of inflammatory and catabolic mediators, such as COX-2 and MMP-13 (36,37). In OA, MMP-13 and COX-2 have a critical role in maintaining cartilage homeostasis (15,38). MMP-13 is involved in type II collagen cleavage, which contributes to the degradation of joint cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years, there are more and more interests in natural products, such as avocado soybean unsaponi ables [16], cordycepin [8], piperine [9], astragalin [10], etc., extracted from herbs as alternatives because of their potential anti-arthritic effects. Evidences have shown the potential role of natural products in the treatment of OA by regulating IL-1β-induced in ammatory mediators [17] [18] [19]. Asiatic acid (AA), a pentacyclic triterpene isolated from various plants including Centella asiatica, has shown anti-in ammation effect in many in ammatory conditions.…”
Section: Introductionmentioning
confidence: 99%